Efektivitas teori konseling cognitive behavior dengan teknik self management untuk meningkatkan disiplin belajar siswa - I Made Putra; Ni Ketut Suarni; I Ketut Dharsana (Jurnal Educatio: Jurnal Pendidikan Indonesia)
This study aims to determine the effectiveness of cognitive behavior counseling theory with self-management techniques to increase student learning discipline. The design of this study used a Quasi-Experimental Design with nonequivalent post-test control group design. The population of this research is the tenth grade students of SMA Negeri 2 Singaraja. Sampling was carried out by random sampling class as an intack group. As for the members of the sample are students of class X5 and X6, totaling 79 people as the experimental class and the control class. The data analysis method used is the t-hit test using the SPSS 25.Windows program. This data collection instrument uses a study discipline questionnaire. So this study uses cognitive behavior counseling theory with self-management techniques to improve learning discipline in class X students of SMA Negeri 2 Singaraja. Based on the results of this study obtained that cognitive behavior counseling with self management technique effective to increase students learning discipline